2016
DOI: 10.1007/s00125-016-3991-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel hepatokine, HFREP1, plays a crucial role in the development of insulin resistance and type 2 diabetes

Abstract: These findings highlight the crucial role of HFREP1 in insulin resistance and diabetes, and provide a potential strategy and biomarker for developing therapeutic approaches to combat these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 26 publications
4
69
0
Order By: Relevance
“…Moreover, it was reported that hepatokines, which are released from the liver, are directly associated with incident type 2 diabetes [35]. Hepatokines, such as selenoprotein P and hepatocyte-derived fibrinogenrelated protein 1, exacerbate hepatic glucose metabolism and insulin signaling, through increasing of hepatic fat accumulation and activation of inflammatory signaling [36,37]. Thus, NAFLD is more associated with incident type 2 diabetes than MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that hepatokines, which are released from the liver, are directly associated with incident type 2 diabetes [35]. Hepatokines, such as selenoprotein P and hepatocyte-derived fibrinogenrelated protein 1, exacerbate hepatic glucose metabolism and insulin signaling, through increasing of hepatic fat accumulation and activation of inflammatory signaling [36,37]. Thus, NAFLD is more associated with incident type 2 diabetes than MetS.…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire was administered by trained nurses in order to obtain data on the demographic characteristics, medical history, and health habits of participants. Since diabetes was reported to be associated with plasma FGL1 concentrations, 19 vector encoding FGL1 increased the fat pad size, whereas FGL1-knockdown by lentiviral vector encoding short-hairpin RNA targeted to FGL1 decreased high-fat dietinduced adiposity. In addition, 3T3-L1 adipocytes were used to clarify the possible mechanism of FGL1-induced adipogenesis.…”
Section: Study Subjectsmentioning
confidence: 99%
“…In addition, FGL1 has a rescue role in hyperglycemic crises . Moreover, we showed that FGL1 has an important role in the development of NAFLD and insulin resistance (IR) . Overexpression of FGL1 in the liver increased hepatic lipid accumulation and IR in mice.…”
Section: Introductionmentioning
confidence: 96%
“…The intraperitoneal glucose tolerance test (IPGTT) and the intraperitoneal insulin tolerance test (IPITT) were performed as previously described [30]. After 12 h of fasting, the mice were intraperitoneally injected either with 1.0 g/kg glucose or 1.0 U/kg insulin.…”
Section: Glucose and Insulin Tolerance Testsmentioning
confidence: 99%